Implementasi Manajemen Sumber Daya Manusia dalam Upaya Meningkatkan Mutu Sekolah di SMP Negeri 5 Semarang - Ni Made Cahyani; Noor Miyono (Melati Institute, 2024)
This study aims 1) to know and analyze the implementation of human resource management in an effort to improve school quality at SMP Negeri 5 Semarang City. 2) to know and analyze the evaluation of the implementation of human resource management in an effort to improve school quality at SMP Negeri 5 Semarang City. The research approach used is qualitative. This type of research is a case study. This research uses triangulation of sources and methods. Data were analyzed using three steps: data reduction, presenting data, and drawing conclusions. The results showed that the implementation of human resource management in an effort to improve school quality at SMP Negeri 5 Semarang showed that 1) the principal by identifying the needs of the school program involved mobilizing all citizens. The principal determines school resources by paying attention and considering the ability and competence of teachers. then the principal conducts organizational development by providing training to teachers, conducting comparative studies to schools that are considered better. Principals give assignments to teachers and delegation always pay attention to the level of ability and expertise of teachers. 2) Evaluation is carried out by conducting monthly meetings then the results of the evaluation of activities are used as a basis for determining follow-up and solutions to be carried out.